(untitled) (Research, Society and Development, 2022)
Diabetes mellitus (DM) is one of the most common Chronic Noncommunicable Diseases (NCDs) in the hospitalization of the Brazilian population. Based on this, it aimed to identify and discuss, through the original reading literature, the relationship between verbal communication of health professionals for diabetes mellitus elderly patients with type 2 in Primary Health. After defining the search criteria and guiding question, a search was carried out in the Latin American and Caribbean Health Sciences Literature (LILACS) and Scientific Electronic Library Online (SCIELO) databases, with the selected collection being submitted to analysis by the Critical Appraisal Skills Programme (CASP). A total of 40 original productions were found, in the period from 2017 to 2021, 10 were selected after careful verification, which are discussed in this review. It was identified, through documentary research, that the main complications in the development of effective communication between the elderly patient and the medical professional are attributed to verbal technicality and the generalization of instructions for care, and it was also evaluated that educational interventions aimed at the sixty-year-old public are the most effective in this area. Furthermore, due to the thematic limitation in the context of medicine, the need to encourage the debate and evolution of the linguistic aspects of communication in continuous professional training is evident.